METHODS AND TOOLS FOR ASSESSING THE LEVEL OF NOISE IMMUNITY OF WIRELESS COMMUNICATION CHANNELS - Knyazev, Vladimir; Lazurenko, Bogdan; Serkov, Aleksandr (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2022)
The subject of this article is the process of increasing the noise immunityof wireless channels in the construction or operation of modern digital communication systems (DCS), when the transmission of digital information significantly complicates the presence of interference and distortion in the communication channel. The aim is analysis and development of methods for ensuring stable and reliable operation of ultra-wideband wireless communication system in the conditions of interference and distortion of information in wireless communication channels. The task is creation and implementation of practical recommendations for improving the level of secrecy and quality of information circulating in the communication channel; development of criteria for quality, information efficiency and noise immunityof DCS wireless communication channels in the conditions of interference of natural and artificial origin. The methods used: methods of analytical modeling and the theory of potential noise immunity. The following results were obtained. The feasibility of assessing the DCS efficiency by two indicators - energy and frequency efficiency, which are the components that make up the overall integral indicator of informational efficiency was shown. It was proposed to evaluate the DCS efficiency by comparing the indicators of informational efficiency of the inverse and reference systems, using the Shannon limit as an ideal ratio of energy and frequency efficiency. On the basis of the theory of potential noise immunity it was shown that it is possible to operate wireless communication channels in conditions when the level of information signal and noise have the same value. Conclusions. It is shown that the use of the technology of supersmooth signals allows to carry out wireless redundant transmission of information with low impromptu capacity. Moreover, the efficiency of digital communication systems significantly increases due to the creation of an ensemble of complex signals through one-time encoding and modulation, which expands its information base, ensuring coverage and energy efficiency in a double symmetric channel. This enables the fullest possible utilization of the channel's Shannon capacity with high integrity of information transfer without a significant increase in the signal-to-noise ratio at the receiver's input. An integral indicator of informational efficiency of the wireless DCS communication channel is provided. It enables real-time integral assessment of link quality and optimal routing in a mobile peer-to-peer network – MANET.